Interactive effect of biocontrol agents in the management of Fusarium rot in cardamom and its impact on plant defense mechanism: Biological control of Fusarium rot in cardamom - Veny Krishna, K C; Dhanya, M K; Joy, M; Radhika, N S; Aparna, B (Journal of Spices and Aromatic Crops, 2021)
Cardamom plantations are subjected to constant threat due to the Fusarium rot disease caused by Fusarium oxysporum Schlecht which is pronounced during summer months. The current study deals with the identification of an effective and ecofriendly management practice for the disease through the use of biocontrol agents. Survey conducted between February and May 2019 revealed maximum disease severity and incidence in Pampadumpara panchayat of Nedumkandam block (84.40% and 100%) and minimum in Erattaar panchayat of Kattappanablock (50.40% and 60.00%). A pot culture experiment was conducted to study the effect of three bioagents (Glomus fasciculatum, Trichoderma asperellum and Pseudomonas fluorescens) individually as well as in combinations. Root inoculation of G. fasciculatum with basal application and spray with P. fluorescens as well as root inoculation of G. fasciculatum along with basal application of T. asperellum and P. fluorescens spray were identifiedto be effective against the disease. Disease suppression by the above bioagents was facilitated by reduced pathogen antagonist ratio in the soil, high level of mycorrhizal colonization in the roots and enhanced biochemical activity of defense enzymes like peroxidase, poly phenol oxidase and phenylalanine ammonia lyase in the plants.